ASQAD MUKHTOR'S METHODOLOGY IN ILLUMINATING WOMEN'S PSYCHOLOGY (Scientific journal of the Fergana State University, 2024)
The article analyzes the image of women in the novel "Birth" by Asqad Mukhtar, one of the major representatives of new Uzbek literature. During the period of reconstruction after the Second World War, that is, in the 50s and 60s of the 20th century, under the slogan of communism, women began to be involved in collective labor on a large scale. This is evident in the appearance of female characters who recognize their rights and act independently. In the novel "Birth", the specific aspects of the mental experiences and situations of such female characters are analyzed.